Diagnostic yield of high-density versus low-density EEG: The effect of spatial sampling, timing and duration of recording. Issue 11 (November 2019) - Bach Justesen, Anders; Foged, Mette Thrane; Fabricius, Martin; Skaarup, Christian; Hamrouni, Nizar; Martens, Terje; Paulson, Olaf B.; Pinborg, Lars H.; Beniczky, Sándor
Highlights: We evaluated the effect of EEG spatial sampling and of recording duration on the diagnostic yield. High-density recordings did not increase the diagnostic yield significantly. Long-term recordings had significantly higher diagnostic yield than short-term recordings. Abstract: Objective: To investigate the effect of spatial sampling and of recording duration on the diagnostic yield of EEG for identification of interictal epileptiform discharges (IEDs). Previous studies demonstrated that high-density (HD) recordings increased accuracy of localization compared to low-density (LD) recordings. Methods: We have prospectively evaluated the effect of spatial sampling and of recording duration in patients who had short-term (ST) recordings with a HD array of 256 electrodes following long-term (LT) recordings with a LD array consisting of the standard IFCN array of 25 electrodes. IED clusters were identified in four datasets: LT-LD, ST-LD (spatially down-sampled to the standard IFCN array), ST-HD and a shortened (90 minutes) epoch of LT-LD. Results: Sixty consecutive patients were recruited. We identified 89 IED clusters totally. Two clusters were found by increasing spatial sampling from 25 to 256 electrodes. This modest increase was not statistically significant. Eight clusters were missed by reducing the recording duration to 90 minutes, as compared with the LT recordings (p = 0.003). Conclusions: Recording duration is more important for the diagnostic yield of EEGs than increasing spatial sampling beyond the standard IFCN electrode array. Significance: The standard IFCN electrode array provides sufficient spatial sampling for identification of the IEDs.